An introduction to the New Testament manuscripts and their texts - Parker, D C (Cambridge University, 2013)
This introduction to the New Testament provides a thorough grounding in the study and editing of the New Testament text combined with an emphasis on the dramatic developments in the field. It covers ancient sources in Greek, Syriac, Latin and Coptic and describes the manuscripts and other ancient textual evidence.